Virtual Reality Design as Digital Learning Media in Preserving Local Culture of Tarawangsa Art - Sumartias, Suwandi; Nugraha, Aat Ruchiat; Bakti, Iriana; Perbawasari, Susie; Subekti, Priyo; Romli, Rosnandar; Paulus, Erick; Aprimulyana, Yuda; Seniwati; Luffiansyah, Prananda; Komalasari, Heni (International Journal of Criminology and Sociology, 2022)
Civilization and culture become significant entities in the historical development of human life. The rapid development of information and communication technology (ICT) has changed the structure of social life in society, including the preservation of Ormatan arts. One of the practical efforts in the preservation of the art of Ormatan is through the media of documentation that utilizes the sophistication of today’s technology. Tarawangsa art, as Sumedang’s original art, began to be rarely performed by the young generation in the village of Rancakalong in particular and Sumedang Regency in general. Therefore, an interactive documentation media is needed to be able to be used as a reference and perpetuation of the Ormatan Tarawangsa art to remain sustainable. One such media is virtual reality (VR). The purpose of designing VR media is to help cultural and cultural actors to have an effective media in socializing the native culture of a particular area so that the moral values contained therein can be sustained. The research method conducted by using a qualitative approach involving Ormatan Tarawangsa art figures and virtual reality media practitioners in a direct participatory manner. The results show that virtual reality media can provide convenience in practising Ormatan Tarawangsa art, which is on the brink of extinction for the younger generation.